STRATEGI PARTAI POLITIK DALAM PEMILIHAN LEGISLATIF TAHUN 2014 (STUDI KASUS PDI PERJUANGAN DI DAPIL II KECAMATAN RUMBAI DAN RUMBAI PESISIR KOTA PEKANBARU) - Afdhal, Said; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study on the legislative elections of 2014 ago, an increase of votes is very significant that experienced by the PDI-P in the City Pekanabru. This is seen in the comparison sounds PDI obtained in 2009 which won 11 551 votes, while in 2014 the PDI-P, said Monday that 30 374 voice sound. the author is trying to formulate questions such as